Being Bullied at School: Gratitude as Potential Protective Factor for Suicide Risk in Adolescents - Rey, Lourdes; Quintana-Orts, Cirenia; Mérida-López, Sergio; Extremera, Natalio (Frontiers in Psychology, 2019)
Bullying victimisation has been recognised as a risk factor for social, physical and psychological problems in adolescence. One promising resource that seems to protect adolescents from adversity and traumatic events is gratitude. However, no analysis of the specific role of gratitude in bullying context has been performed as yet. Thus, the aim of this research was to explore the associations between bullying victimisation, gratitude and suicide risk (i.e., depressive symptoms and suicidal thoughts and behaviours) and gender-based differences. We also investigated whether levels of gratitude moderated the relationship between victimisation and suicide risk for girls and boys. A convenience sample of 1,617 adolescents (50.5% girls; Mage = 14.02) participated in this research. Adolescents completed a paper-and-pencil questionnaire about their bullying victimisation, gratitude, depressive symptoms and suicidal thoughts and behaviours. Gratitude was found to be negatively related to victimisation and suicide risk. While no gender differences were found in gratitude, it was observed that girls reported higher levels of suicide risk. However, the victimisation x gratitude interaction contributed to variance in suicide risk, but only for girls: Those girls who were victims of bullying with high gratitude scores reported lower suicide risk than their counterparts who showed less gratitude. Thus, the findings from this present cross-sectional study suggest that gratitude is related to suicide risk in the context of bullying victimisation, especially among adolescent girls. Finally, the theoretical and practical implications of our novel contributions to the understanding of gratitude as a protective factor against consequences of bullying victimisation are discussed. Keywords: bullying victimisation, suicidal thoughts and behaviours, depressive symptoms, gratitude, adolescence